2022
DOI: 10.24018/ejbio.2022.3.5.399
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Partial Characterization of Tannase produced by Aspergillus niger SCSGAF0145 using Arachis hypogaea (Groundnut) Shell

Abstract: Tannase have been widely secreted industrially by fungi using tannin rich agricultural waste as substrate. Aspergillus niger SCSGAF0145, was used for the secretion of tannase using groundnut shell as substrate under submerged fermentation. The crude tannase secreted was precipitated out using ammonium sulphate and purified on Sephadex G-150. Kinetic parameters of the secreted tannase were determined using tannic acid as substrate. The estimated biomass weight, tannin concentration, gallic acid concentration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…By utilising DEAE cellulose, ion exchange chromatography to purify the crude enzyme to homogeneity, 37.39% enzyme yield was achieved with a purification fold of 21.23, which was the same as that of pure tannase from a variety of fungi and bacteria (Govindarajan et al, 2019). Our findings were comparable to purified tannase obtained from Bacillus haynesii SSRY4 MN031245, which demonstrated a purification fold of 42.0 with 36.30% of enzyme yield (Dhiman et al, 2022) and tannase produced from Aspergillus niger SCSGAF0145, which demonstrated a 47.86% yield and 13.44 folds purification (Olaleye et al, 2022).…”
Section: Purification Of Enterobacter Hormaechei Z8b-60 Tannasesupporting
confidence: 79%
“…By utilising DEAE cellulose, ion exchange chromatography to purify the crude enzyme to homogeneity, 37.39% enzyme yield was achieved with a purification fold of 21.23, which was the same as that of pure tannase from a variety of fungi and bacteria (Govindarajan et al, 2019). Our findings were comparable to purified tannase obtained from Bacillus haynesii SSRY4 MN031245, which demonstrated a purification fold of 42.0 with 36.30% of enzyme yield (Dhiman et al, 2022) and tannase produced from Aspergillus niger SCSGAF0145, which demonstrated a 47.86% yield and 13.44 folds purification (Olaleye et al, 2022).…”
Section: Purification Of Enterobacter Hormaechei Z8b-60 Tannasesupporting
confidence: 79%